UTAUT and WebQual Models for Measuring User Acceptance of Text Minutes from Video Conferencing Services - Ningsih, Dewi Handayani Untari; Nurdin, Alya aulia; Muslim, Much Aziz (Universitas Negeri Semarang, 2023)
One of the issues encountered during the post-COVID-19 and new normal period is in the field of higher education and employment that require education and online or virtual meetings. Automatic speech recognition (ASR) is one of the technologies used to simplify recording through speech recognition into text minutes for the effectiveness of online meetings. This study aims to determine user acceptance in adopting text minutes on the Zoom Meeting video conference service for online meetings so that it can provide insights for video conferencing service provider companies in developing text minutes on their platforms. In this study, a total of 156 respondents participated in the study. The obtained data were analyzed using PLS-SEM. As a result, the construct of information, interaction, and performance expectancy has been shown to affect user satisfaction with text minutes in video conferencing services with an R square value of satisfaction of 0.516 (moderate). The quality of information is an important factor, information from the text minutes on video conferencing services must be accurate, reliable, timely, relevant, easy to understand, and presented in the appropriate format.Purpose: This observes ambitions to determine consumer popularity in adopting text minutes at the Zoom assembly video conference provider for online meetings in order that it could offer insights for video conferencing carrier company organizations in developing text minutes on their structures.Methods/Study design/approach: This study uses a mixture of UTAUT and WebQual. A studies instrument becomes prepared inside the shape of a web questionnaire containing query objects. All the items had been adapted from previous research. Then, data became amassed by way of administering an online questionnaire through diverse social media structures, along with WhatsApp and Telegram to respondents with several demographic questions and a five-factor Likert scale from strongly disagree to strongly agree (scored from 1 to 5) from eleven constructs. The obtained facts had been analyzed the usage of PLS-SEM.Result/Findings: The existence of text minutes on the Zoom Meeting video conference service has not been fully adopted by users in carrying out learning activities or online meetings. Primarily based on the studies that have been executed, there are four hypotheses accepted, namely H2, H3, H5, and H10. Meanwhile, six different hypotheses, namely H1, H4, H6, H7, H8, and H9, have been rejected. Elements influencing person adoption of the text of the Zoom assembly video conferencing carrier depend on the nice of the information generated from the text minutes from video conferencing in which the statistics ought to be accurate, reliable, well timed, relevant, easy to apprehend, and provided in the right format. Novelty/Originality/Value: As a result, the construct of information, interaction, and performance expectancy has been shown to affect user satisfaction with text minutes in video conferencing services with an R square value of satisfaction of 0.516 (moderate). From the outcomes of the research conducted, video conferencing service providers can improve and expand text mins capabilities extra sophisticatedly but nonetheless easy in order that overall customers sense greater satisfied with video conference textual content mins and could reuse and endorse others to apply the same era. In the next look at, its miles predicted that the scope of the survey will be wider globally with the growth within the wide variety of respondents, in addition to including a few constructs that have now not been used